Micro strip antenna design for UWB with improved bandwidth - Sahoo, Swarnaprava; Prasad Mishra, Laxmi (International Journal of Engineering and Technology, 2018)
An UWB planar antenna is designed for bandwidth improvement using micro strip radiator. The radiator is designed with epoxy FR- 4 dielectric substrate. The geometry is of rectangular patch with semi round slot at each corner along with a rectangular slot in partial ground plane. The simulation bandwidth is 12.1 GHz and varies from 3.2 GHz to 15.3 GHz. The simulated result shows that the maximum gain achieves 5.4 dB at 14.3 GHz. The radiation characteristics are almost omnidirectional and dipole shape in H- and E- plane respectively. The simulation is carried out with HFSS simulator.Â Â Â